Educational Innovation, Underestimated: Analysis of the Importance Given by Students of Journalism - Roses, Sergio; Humanes, María Luisa (Historia y Comunicación Social, 2014)
This research examines the attitudes of Journalism students towards educational innovation with a cross-national survey in seven countries. The goal is to observe the importance given by students to the educational innovation among a set of tasks, which professors have to develop in their academic work. The Spanish Journalism students underestimated the relevance of educational innovation. Women gave more importance to innovation in education than men. No differences were found among five Spanish universities.
Keywords: Educational Innovation; Journalism; University Students; EHEA; Attitudes; Teaching innovation